1993
DOI: 10.1063/1.109660
|View full text |Cite
|
Sign up to set email alerts
|

Light emitting nanocrystalline silicon prepared by dry processing: The effect of crystallite size

Abstract: A new technique for the preparation of light emitting nanocrystalline (nc) silicon by a combination of plasma chemical vapor deposition and post-treatment consisting of oxidation and annealing in forming gas is reported. The advantage of this processing consists in the possibility of a control of the crystallite size and the fraction of nc-Si in the film. A strong increase of the photoluminescence below 35 Å, as predicted by theory, is documented experimentally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(28 citation statements)
references
References 26 publications
3
25
0
Order By: Relevance
“…[127] annealing. [132] It should be noted that nc-Si is commonly produced by ion implantation, [133] electrochemical etching, [134] and chemical vapor deposition, [135] all of which are suitable for low-dimensional nanostructures such as porous Si and Si dots. It is important to emphasize that the nano-grained semiconductors were obtained in bulk form by virtue of HPT.…”
Section: Mg and Mgmentioning
confidence: 99%
“…[127] annealing. [132] It should be noted that nc-Si is commonly produced by ion implantation, [133] electrochemical etching, [134] and chemical vapor deposition, [135] all of which are suitable for low-dimensional nanostructures such as porous Si and Si dots. It is important to emphasize that the nano-grained semiconductors were obtained in bulk form by virtue of HPT.…”
Section: Mg and Mgmentioning
confidence: 99%
“…Several techniques for making nc-Si have been explored, including gas-phase production via the thermal decomposition of silanes 2,3 and microwave plasma decomposition of silane, 4 Si deposition in the presence of large partial pressures of hydrogen, 5,6 spark ablation of c-Si surfaces, 7 laser and thermal crystallization of amorphous silicon/silicon nitride layers, 8 and Si-rich oxide layers. 9,10 Studies of the materials produced by these techniques have shown that nc-Si does luminesce strongly in the red on the microsecond time scale, and sometimes blue 11 on the nanosecond time scale, 12 when successfully passivated to minimize rapid nonradiative surface recombination.…”
Section: Introductionmentioning
confidence: 99%
“…The sample preparation was described in our earlier papers [1,2,[15][16][17]. Thus only a brief summary is given here.…”
Section: Methodsmentioning
confidence: 99%